Escherichia coli Inactivation by UVC-Irradiated C60: Kinetics and Mechanisms - Cho, Min; Snow, Samuel D; Hughes, Joseph B; Kim, Jae-Hong (Environmental science & technology, 2011)
Motivated by recent studies that documented changes in fullerene toxicity after chemical transformation, C60 aggregates (nC60) were subject to UVC irradiation at monochromatic 254 nm and subsequently evaluated for antibacterial and bactericidal properties against Escherichia coli. The nC60 treated with UVC irradiation, referred to herein as UVC-irradiated C60, did not directly inhibit bacterial growth at concentrations up to 20 mg/L. In the presence of UVA and visible light, however, UVC-irradiated C60 rapidly inactivated E. coli, suggesting that photochemical production of reactive oxygen species (ROS) was involved. The use of ROS scavengers and probes determined that hydroxyl radicals were the primary ROS responsible for the E. coli inactivation. Results from protein release, lipid peroxidation, cell permeability, and intracellular enzyme assays suggest that the inactivation mechanism involves UVC-irradiated C60 diffusing through E. coli cell membrane and producing hydroxyl radicals within the cell. Further study on water-soluble C60 derivatives and possible transformative processes is, therefore, recommended based on the environmental implications of results presented herein that nC60 exposed to UVC irradiation is more toxic than parent nC60.